ISLAMIC RELIGIOUS COPING STRATEGY FOR HEALTHCARE WORKER IN COVID-19 PANDEMIC: A LITERATURE REVIEW - Nopa, Ika; Siregar, Pinta Pudiyanti (International Islamic Medicine Forum, 2021)
On March 11, 2020, WHO announced that COVID-19 was a pandemic. Healthcare workers were directly exposed to the impacts and dangers of the COVID-19 pandemic. It is important to know effective stress coping for healthcare workers to provide maximum health services. Religiosity was commonly used by healthcare workers for coping strategic COVID-19 Pandemic Religious beliefs and practices have become a powerful coping strategy among nurses. Religion could be an element of resilience for healthcare workers and served as a protective factor. Religiosity will reduce cortisol level as a biomarker of stress. For Muslim healthcare workers, stress reduction can be done by praying, salat, reading, and listening to the Holy Qur’an. Studies show that the tahajud prayer significantly reduce stress and listening to Surah Al-Rahman was significantly reduce cortisol level. Facing the COVID-19 pandemic, hospitals with Muslim healthcare workers can provide time and facilities to pray and play the Holy Qur’an in to reduce work stress.